1997
DOI: 10.1104/pp.115.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Actin Filaments Modulate Both Stomatal Opening and Inward K+-Channel Activities in Guard Cells of Vicia faba L

Abstract: Actin antagonists have previously been shown to alter responses of Commelina communis stomata to physiological stimuli, implicating actin filaments i n the control of guard cell volume changes (M. Kim, P.K. Hepler, 5-0. Eun, K.S. Ha, Y. Lee [1995] Plant Physiol 109: 1077-1084). Since K+ channels i n the guard cell play an important role i n stomatal movements, we examined the possible regulation of K+-channel activities by the state of actin polymerization. Agents affecting actin polymerization altered light-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 35 publications
(31 reference statements)
7
84
0
Order By: Relevance
“…Under a hypertonic condition, actin filaments in the protoplasts are organized into a network configuration that corresponds to a small I Kin and a small stomatal aperture. The correlation of actin filament organization in guard cells and stomatal aperture under normal conditions was described by Lee and colleagues (Kim et al 1995;Hwang et al 1997) and is consistent with the osmosensing mechanism observed by Liu & Luan (1998). Although actin filament organization is linked to the ion channel regulation in both animal and plant cells, little is understood on the molecular mechanism underlying actin-ion channel interaction.…”
Section: Osmosensing Of Ion Channels: An Aba-independent Pathwaysupporting
confidence: 56%
“…Under a hypertonic condition, actin filaments in the protoplasts are organized into a network configuration that corresponds to a small I Kin and a small stomatal aperture. The correlation of actin filament organization in guard cells and stomatal aperture under normal conditions was described by Lee and colleagues (Kim et al 1995;Hwang et al 1997) and is consistent with the osmosensing mechanism observed by Liu & Luan (1998). Although actin filament organization is linked to the ion channel regulation in both animal and plant cells, little is understood on the molecular mechanism underlying actin-ion channel interaction.…”
Section: Osmosensing Of Ion Channels: An Aba-independent Pathwaysupporting
confidence: 56%
“…The physical state of actin in animal cells affects activities of lipidhydrolyzing enzymes, receptor-and nonreceptor-protein kinases, G-proteins, and their modulators (Carraway and Carraway, 1995), as well as ion channels (Cantiello et al, 1991;Schwiebert et al, 1994;Prat et al, 1996). Our patchclamping data showed that activities of K + channels in guard cells are certainly influenced by application of actin antagonists (Hwang et al, 1997). We are currently investigating other possible target molecules of actin in guard cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent elegant studies with transiently expressed GFP-tagged KAT1 and dominant negative SNARE fragments show that KAT1 is localized at the PM in punctuate structures and that syntaxins regulate the trafficking and clustering of these channels [41]. Actin cytoskeleton stability also plays a role in K + channel regulation: drugs that induce actin cytoskeleton depolymerization (cytochalasin D) increase inward K + currents in Vicia faba guard cells, whereas phalloidin, which stabilizes the actin cytoskeleton, inhibits these currents [42,43], and perhaps these effects reflect alterations in K + channel trafficking (Fig. 3) cyt .…”
Section: K + Channels: Properties and Regulationmentioning
confidence: 99%